Analysis Of Factors That Influence The Effectiveness Of Accounting Information Systems In Village Credit Institutions - Ernawatiningsih, Ni Putu Lisa; Sunarwijaya , I Ketut (Universitas Pendidikan Ganesha, 2024)
The purpose of this study was to determine the analysis of factors that influence the effectiveness of accounting information systems at Village Credit Institutions in Denpasar City. This study was conducted at Village Credit Institutions in Denpasar City, there are 35 LPDs in 4 Districts, namely North Denpasar District, East Denpasar District, South Denpasar District and West Denpasar District. Data collection uses primary data in the form of questionnaires. The sampling method used in this study is the purposive sampling technique. The number of samples selected was 237 respondents. The data analysis technique used is multiple linear regression analysis technique. The results of the study indicate that the sophistication of information technology and knowledge of accounting employees do not affect the effectiveness of AIS at Village Credit Institutions in Denpasar City. While user participation, training and work experience have a positive effect on the effectiveness of AIS at Village Credit Institutions in Denpasar City.